Immune monitoring alongside factors associated with upper respiratory illness in elite swimmers, over an 8-month training period leading into competition - Baker, L. H.; Wells, A. V.; Desai, T. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Upper respiratory illness (URI) is the most frequently reported illness in athletes, resulting in lost training time and reduced success at competition. Due to the high physical demands on elite swimmers, individual athletic monitoring of mucosal immunity and identifying risk factors of URI is paramount. Therefore, the current study investigated the effect of training load (TL), sleep and Epstein Barr Virus (EBV) status on salivary immunoglobulin A (sIgA) and self-reported upper respiratory symptoms (URS).